Eyes on CHARGE syndrome: Roles of CHD7 in ocular development - Krueger, Laura A.; Morris, Ann C. (Frontiers in Cell and Developmental Biology, 2022)
The development of the vertebrate visual system involves complex morphogenetic interactions of cells derived from multiple embryonic lineages. Disruptions in this process are associated with structural birth defects such as microphthalmia, anophthalmia, and coloboma (collectively referred to as MAC), and inherited retinal degenerative diseases such as retinitis pigmentosa and allied dystrophies. MAC and retinal degeneration are also observed in systemic congenital malformation syndromes. One important example is CHARGE syndrome, a genetic disorder characterized by coloboma, heart defects, choanal atresia, growth retardation, genital abnormalities, and ear abnormalities. Mutations in the gene encoding Chromodomain helicase DNA binding protein 7 (CHD7) cause the majority of CHARGE syndrome cases. However, the pathogenetic mechanisms that connect loss of CHD7 to the ocular complications observed in CHARGE syndrome have not been identified. In this review, we provide a general overview of ocular development and congenital disorders affecting the eye. This is followed by a comprehensive description of CHARGE syndrome, including discussion of the spectrum of ocular defects that have been described in this disorder. In addition, we discuss the current knowledge of CHD7 function and focus on its contributions to the development of ocular structures. Finally, we discuss outstanding gaps in our knowledge of the role of CHD7 in eye formation, and propose avenues of investigation to further our understanding of how CHD7 activity regulates ocular and retinal development.